Dysbiosis of skin microbiome and gut microbiome in melanoma progression - Mekadim, Chahrazed; Skalnikova, Helena Kupcova; Cizkova, Jana; Cizkova, Veronika; Palanova, Anna; Horak, Vratislav; Mrazek, Jakub (BMC microbiology, 2022)
BACKGROUND: The microbiome alterations are associated with cancer growth and may influence the immune system and response to therapy. Particularly, the gut microbiome has been recently shown to modulate response to melanoma immunotherapy. However, the role of the skin microbiome has not been well explored in the skin tumour microenvironment and the link between the gut microbiome and skin microbiome has not been investigated in melanoma progression. Therefore, the aim of the present study was to examine associations between dysbiosis in the skin and gut microbiome and the melanoma growth using MeLiM porcine model of melanoma progression and spontaneous regression. RESULTS: Parallel analysis of cutaneous microbiota and faecal microbiota of the same individuals was performed in 8 to 12 weeks old MeLiM piglets. The bacterial composition of samples was analysed by high throughput sequencing of the V4-V5 region of the 16S rRNA gene. A significant difference in microbiome diversity and richness between melanoma tissue and healthy skin and between the faecal microbiome of MeLiM piglets and control piglets were observed. Both Principal Coordinate Analysis and Non-metric multidimensional scaling revealed dissimilarities between different bacterial communities. Linear discriminant analysis effect size at the genus level determined different potential biomarkers in multiple bacterial communities. Lactobacillus, Clostridium sensu stricto 1 and Corynebacterium 1 were the most discriminately higher genera in the healthy skin microbiome, while Fusobacterium, Trueperella, Staphylococcus, Streptococcus and Bacteroides were discriminately abundant in melanoma tissue microbiome. Bacteroides, Fusobacterium and Escherichia-Shigella were associated with the faecal microbiota of MeLiM piglets. Potential functional pathways analysis based on the KEGG database indicated significant differences in the predicted profile metabolisms between the healthy skin microbiome and melanoma tissue microbiome. The faecal microbiome of MeLiM piglets was enriched by genes related to membrane transports pathways allowing for the increase of intestinal permeability and alteration of the intestinal mucosal barrier. CONCLUSION: The associations between melanoma progression and dysbiosis in the skin microbiome as well as dysbiosis in the gut microbiome were identified. Results provide promising information for further studies on the local skin and gut microbiome involvement in melanoma progression and may support the development of new therapeutic approaches.
Keywords: Bacteria; NGS; Gastrointestinal Microbiome; Feces; Gut microbiome; Tumour microenvironment; Animals; Skin microbiome; Skin cancer; melanom; Tumor Microenvironment; Melanoma; MeLiM; RNA ribozomální 16S; Swine; Fusobacterium; RNA, Ribosomal, 16S; mikrobiota; Pig; feces; Metagenomic analysis; zvířata; prasata; Dysbiosis; dysbióza; Microbiota; nádorové mikroprostředí; Gut-skin axis; střevní mikroflóra